2016
DOI: 10.4236/aim.2016.61005
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotia Formation and Toxin Production in Large Sclerotial <i>Aspergillus flavus</i> Isolates from Kenya

Abstract: We studied the relationship between sclerotia formation and aflatoxin production by Aspergillusflavus strains isolated from maize kernels from Nandi County. Isolates recovered from maize kernels were tested for their ability to form sclerotia on different growth media. PCR analysis was done on the isolates to detect 2 structural genes, aflD and aflQ, involved in aflatoxin biosynthesis pathway. Positive A. flavus isolates for one or both genes were grown on Yeast Extract Sucrose Agar medium and aflatoxins quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…A previous study reported that strains of A. flavus consist of biseriate and uniseriate strains [8]. However, most uniseriate and L strains were observed in this study.…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…A previous study reported that strains of A. flavus consist of biseriate and uniseriate strains [8]. However, most uniseriate and L strains were observed in this study.…”
contrasting
confidence: 69%
“…However, most uniseriate and L strains were observed in this study. Fifty-eight percent (7 of 12) A. flavus strains isolated from unirradiated and irradiated kernel formed Large (L) sclerotia and 5 of 12 strains were non-sclerotial producers as it was reported in other studies [8]. Odhiambo et al [9] differentiate toxigenic and non-toxigenic A. flavus strains based on yellow pigment formation using PDA medium.…”
mentioning
confidence: 90%
“…The cobs were kept at room temperature and examined the day after collection. The sweet corn kernels were sampled from different parts of the cob using closed spear driven through to the top and sides to obtain 300 g of incremental samples [26]. All the samples were randomly sampled.…”
Section: Sweet Corn Kernelsmentioning
confidence: 99%
“…There is a general poor awareness about aflatoxins, let alone the dissemination of appropriate control measures to monitor contamination at the field level, during storage, and in commercialisation. Primary health care centers in Africa almost never relate liver cancer or other negative health effects to food consumption and aflatoxin [18,19]. Knowledge in most African countries is only high in areas where outbreaks have occurred in the past and this also depends on the level of education.…”
Section: Awareness On Aflatoxin Contaminationmentioning
confidence: 99%